2015
DOI: 10.1002/2015gl064964
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric intrusions, the Santa Ana winds, and wildland fires in Southern California

Abstract: The Santa Ana winds of Southern California have long been associated with wildland fires that can adversely affect air quality and lead to loss of life and property. These katabatic winds are driven primarily by thermal gradients but can be exacerbated by northerly flow associated with upper level troughs passing through the western U.S. In this paper, we show that the fire danger associated with the passage of upper level troughs can be further increased by the formation of deep tropopause folds that transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
2
30
1
Order By: Relevance
“…A recent study suggested that the coupling between Santa Ana winds and stratospheric intrusions might pose serious O 3 pollution threats across the coast of southern California (22). In this study, groundlevel O 3 mixing ratios during the Santa Ana event increased significantly (Fig.…”
Section: Field-based 35 S Measurementssupporting
confidence: 51%
See 3 more Smart Citations
“…A recent study suggested that the coupling between Santa Ana winds and stratospheric intrusions might pose serious O 3 pollution threats across the coast of southern California (22). In this study, groundlevel O 3 mixing ratios during the Santa Ana event increased significantly (Fig.…”
Section: Field-based 35 S Measurementssupporting
confidence: 51%
“…Such deep stratospheric intrusion events compromise high-altitude regions of the western United States in attaining US National Ambient Air Quality Standard (NAAQS) for O 3 (6). Additional field-based observation studies indicated that this O 3 -rich stratospheric air can even be transported to lowaltitude regions, such as Los Angeles at the southern California coast (8,22,23). Consequently, this region is a natural laboratory for studying the potential of 35 S as a tracer for stratospheric intrusions.…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…In the case of deep stratospheric intrusions, ozone-rich stratospheric air masses embedded in the lower half of the fold can reach lower altitudes, and occasionally the planetary boundary layer mixing down to the surface (Chung and Dann, 1985;Langford et al, 2012Langford et al, , 2015Lefohn et al, 2012;Lin et al, 2012a), leading to an ozone increase in the lower troposphere (Fig. 14b).…”
Section: The Influence Of Tropopause Folds On the Tmf Tropospheric Ozmentioning
confidence: 99%